Students’ metacognitive knowledge of learning-strategy effectiveness and their recall of teachers’ strategy instructions - Olop, Joosep; Granström, Mikk; Kikas, Eve (Frontiers in Education, 2024)
This study aimed to investigate students’ metacognitive knowledge and reported use of surface and deep learning strategies. It also explored the extent to which students recall their teachers’ recommendations for learning strategies and the relationship between these recollections and students’ knowledge and reported use of strategies. A scenario-based questionnaire was used to set a learning goal in the area of biology. Students’ metacognitive knowledge was assessed through perceived effectiveness and reported use of learning strategies. Additionally, open-ended questions allowed students to recall and report recommendations given by their teachers. We used person-centered methods to explore whether different types of recollections were related to reported strategy use. Among students who recollected that their teachers have recommended deep learning strategies, it was typical to value deep strategies higher than surface strategies and report using deep strategies. Also, it was atypical among those students to value surface level strategies and not use deep strategies.